EXAMINING INTERRELATED DRIVING FORCES FOR SUSTAINABLE SCHOOL IMPROVEMENT: Received: 08th August 2023, Revised: 28th November 2023, 5th December 2023, 19th December 2023, Accepted: 24th August 2023 - Osman, Mohamed El Tahir (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This research is part of a comprehensive project whose goal is to analyze and activate the interconnected elements within the education system that foster student empowerment in the Sultanate of Oman. The project proposed that sustained enhancements in the education system hinge on a collection of interlinked subsystems or factors that collectively boost overall school performance and student learning (Osman, 2023). The primary aim of this investigation was to scrutinize the interrelated elements capable of expanding the educational environment and contributing to long-lasting improvements in schools. The study adopted a descriptive-analytical approach, combining both qualitative and quantitative data analysis techniques. The study’s sample comprised 110 educators and administrators from the participating experimental schools. The results indicate that the 13 factors examined in the proposed model make significant contributions to viable school improvement. Nevertheless, the importance of these factors varies from one to another. Based on these findings, it can be argued that activating all interrelated elements within the education system is imperative for achieving enduring improvements in student learning over time. Therefore, it is crucial to systemically enhance the performance of all interconnected factors within the education system.